Implementation of Internet of Things in the Production Process of MSMEs: Quality Improvement and Process Control - Mardiani, Eri; D.Iwan Riswandi; Degdo Suprayitno; Khamaludin; Halim Mudia (Jurnal Informasi dan Teknologi, 2024)
This research explores the application of IoT in MSME production to enhance quality and process control. The focus is on addressing challenges such as high costs, lack of technical understanding, and data security. The aim is to highlight the benefits of IoT, evaluate implementation challenges, and provide strategic guidance for MSMEs to thrive in the digital era. This research adopts a descriptive qualitative approach using purposive area sampling, focusing on Surabaya, an industrial city supported by the government for MSMEs. The goal is to understand the application of IoT in improving quality and process control in Surabaya MSMEs. This research method provides in-depth insights into the observed phenomena aligned with the objectives set. Awareness and adoption of IoT in MSMEs are low due to constraints such as technological understanding, costs, data security, and lack of perceived benefits. Barriers include limited technical knowledge, high costs, and data security concerns. Solutions include enhancing technological understanding, integrating ERP, and utilizing IoT-based quality control systems. MSMEs can improve their efficiency, quality, and competitiveness with the right strategy. Implementing IoT technology can enhance MSMEs' quality, process control, operational efficiency, and competitiveness. MSMEs are advised to carefully plan and implement IoT solutions, considering their needs and potential benefits, and collaborate with experienced technology solution providers to address technical and operational challenges.